2022
DOI: 10.1101/2022.10.06.511108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feedback-based motor control can guide plasticity and drive rapid learning

Abstract: Animals use afferent feedback to rapidly correct ongoing movements in the presence of a perturbation. Repeated exposure to a predictable perturbation leads to behavioural adaptation that counteracts its effects. Primary motor cortex (M1) is intimately involved in both processes, integrating inputs from various sensorimotor brain regions to update the motor output. Here, we investigate whether feedback-based motor control and motor adaptation may share a common implementation in M1 circuits. We trained a recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…In fact, our results using weight perturbation for retraining inputs were inspired by previous work on slow, noisy cerebellar-dependent adaptation [89, 90]. Alternative computational theories also suggest that cerebellar feedback may guide subsequent local plasticity within M1, either by acting as a teaching signal [91, 92] or by estimating surrogate gradients for weight updates [93]. Nonetheless, better characterisation of cortico-cerebellar interactions during BCI control as well as learning is a promising next step.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In fact, our results using weight perturbation for retraining inputs were inspired by previous work on slow, noisy cerebellar-dependent adaptation [89, 90]. Alternative computational theories also suggest that cerebellar feedback may guide subsequent local plasticity within M1, either by acting as a teaching signal [91, 92] or by estimating surrogate gradients for weight updates [93]. Nonetheless, better characterisation of cortico-cerebellar interactions during BCI control as well as learning is a promising next step.…”
Section: Discussionmentioning
confidence: 58%
“…While we exclusively modelled upstream plasticity as the basis of adaptation, it is likely there are concurrent distributed changes, particularly for longer- timescale learning. Several computational studies have suggested error- or reward-based modulation of local connectivity in M1 during motor adaptation [92, 100, 101]. Modelling these parallel learning processes and dissecting the multi-region circuits underlying learning is an exciting avenue for future work.…”
Section: Discussionmentioning
confidence: 99%